Optimization of Biogas Production from Organic Municipal Waste: Development of Activated Sludge as Digesters Inoculum - BABA-MOUSSA, FARID A. KADER; ADEOTI, ADEOLA ZOURI-KIFOULI (My University, 2017)
This study is a contribution to the optimization of organic fraction of municipal waste bioconversion into biomethane, by activated sludge production as inoculum for digesters. The wastewater (WW) and cow dung (CD) samples were taken from the slaughterhouse of Ouagadougou town, Burkina Faso. Different mixtures were made, enriched with mineral solution and cellulose at 5% (w/v) as: 10% CD + 90% WW (C7), 30% CD + 70% WW (C6), 50% CD + 50% WW (C5), 70% CD + 30% WW (C4), 90% CD + 10% WW (C3), 100% CD (C2) and 100% WW (C1). The pH evolution and biogas (CH4 and CO2) production were followed for 25 days. Cultures tend to acidify with increase in cow dung proportion. Biogas production was significantly higher (p < 0.05) in C5 (880.0 mL), C6 (862.0 10 mL) and C7 (772.0 mL). Mixture C5 had a highest level of CO2 production (40%). Also C7 and C6 retained in the experiment contained respectively organic matter, volatile fatty acids (VFA) and total alkalinity (TAC) as 41.06%, 47.02%, 1320 mg acetic acid/L, 3036 mg Acetic acid/L and 520 mg CaCO3/L, 1310 mg CaCO3/L. Mixture C6 was the best medium for microorganism proliferation stability with 3.5 × 105 UFC/ml of methanogens bacteria. It also possessed buffering capacity, which prevents acidification of medium during VFAs production.
Keywords: Bioconversion; Municipal Waste; Activated Sludge; Biomethane; Burkina Faso